Methods and instruments for the transformative design of the public space: insight from the Ancient Canal of Yangzhou in China - Fanzini, Daniele; Miao, Siqi; Casoni, Giorgio (Frontiers in Built Environment, 2024)
This study applies transformative technologies, specifically Geographic Information Systems (GIS) and environmental psychology tools, within the Yangzhou Canal area, enhancing public space utility and resident satisfaction. Using a mixed-methods approach, including a survey with 213 responses and field observations, we explored the socio-psychological impacts of the canal as a historic urban landscape. Questionnaire responses revealed correlations between the spatial characteristics and their usage, perceived and actual uses of space, exploring the canal's cultural value, visiting methods and temporality, social and spatial characterization, and the residents' preferences for different canal spaces. Observational studies at three key sites highlighted distinct patterns in activity and engagement, offering insights into locals' preferences and behaviors. The findings contribute to urban design by providing a research framework that integrates historical canals with contemporary urban life, ultimately enhancing community satisfaction and livability. This study introduces a novel approach by systematically implementing GIS and environmental psychology to analyze and improve public spaces.